Genetic parameters of 305 days and monthly test-day milk yields in Murrah buffaloes - SINGH, MANVENDRA; SINGH, AVTAR; GUPTA, A K; DASH, S K; SHIVAHRE, P R; SAHOO, SAROJ KU; AMBHORE, G S (The Indian Journal of Animal Sciences, 2016)
The present investigation was carried out using first lactation 9,071 monthly test-day milk yield records of 965 Murrah buffaloes that calved from 1977 to 2012 sired by 98 bulls maintained at ICAR-National Dairy Research Institute, Karnal. Mixed model analysis was carried out by least-squares maximum likelihood programme to study the effects of genetic and non-genetic factors on first lactation 305-day milk yield and monthly test-day (TD) milk yield records of Murrah buffaloes. The highest monthly test-day milk yield was observed in TD3 (7.64 kg) and lowest in TD10 (4.46 kg). The average first lactation 305 days or less milk yield (FL305DMY) was 1806.45±16.99 kg. The effect of season of calving, period of calving and age at first calving was highly significant on FL305DMY and on most of the monthly test-day milk yields. The heritability estimate for FL305DMY was 0.18±0.08 and for monthly test-day milk yields it ranged from 0.09 (TD6) to 0.18 (TD3). The genetic and phenotypic correlations among monthly test-day milk yields and with 305 days milk yield were highly significant. The present investigation revealed that the non-genetic factors such as season of calving in general and year of calving in particular, might be considered when performing an evaluation of Murrah buffaloes based on monthly test-day milk yield records. High genetic and phenotypic correlation among monthly test-day milk yields and with first lactation 305 days milk yield suggested that these test-day yields could be used as the selection criteria, leading to a reduction in generation interval.